OBTURATOR HOOK SIGN — WHEN THE COMMON ILIAC VEIN DISAPPEARANCE ELUDES VISUAL DETECTION
Introduction: Diagnosis of chronic iliac venous outflow obstruction is challenging, and no ideal imaging method has yet been defined. Even with imaging with superb detail, common iliac vein disappearance as occurs in Post-Thrombotic Syndrome (PTS) may be missed even by the most experienced radiologist. This scanning error occurs due to psychophysiological factors of human visual perception. The purpose of this paper is to report on the “obturator hook sign”, evidencing obturator vein engorgement as a collateral pathway and hence a marker for hemodynamically significant chronic iliac venous outflow lesion, supporting this diagnosis. Methods: Retrospective review of Indirect and Direct Computed Tomography Venography (CTV) and Magnetic Resonance Venography (MRV) imaging of the obturator hook sign and comprehensive literature review regarding iliac vein outflow obstruction diagnosis focusing on collateral vein development. Results : The obturator hook sign is identified in Direct CTV, Indirect CTV and MRV of patients with chronic iliac venous outflow obstruction. The sign was never identified in imaging studies with no chronic iliac obstruction, suggesting high specificity. Discussion: Venous collateralization is poorly understood, but it has been shown that when the main venous path is stenosed or occluded and the venous pressure rises, flow is side-tracked through alternative pathways. When the main venous path lesion is stented, flow once again takes the lower resistance pathway and the collaterals withdraw. The obturator hook sign can be easily recognisable in CTV and MRV due to its peculiar anatomy and immediately points us towards hemodynamically significant chronic iliac venous outflow obstruction.